2019
DOI: 10.3390/jmse7070225
|View full text |Cite
|
Sign up to set email alerts
|

Steps towards Modeling Community Resilience under Climate Change: Hazard Model Development

Abstract: With a growing population (over 40%) living in coastal counties within the U.S., there is an increasing risk that coastal communities will be significantly impacted by riverine/coastal flooding and high winds associated with tropical cyclones. Climate change could exacerbate these risks; thus, it would be prudent for coastal communities to plan for resilience in the face of these uncertainties. In order to address all of these risks, a coupled physics-based modeling system has been developed that simulates tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…This is not a true "total water level" simulation, as waves were not included; however, as the focus of this study is to provide general proof of concept and validation of the methodology rather than a true hindcast validation of the near-shore coastal response, the lack of wave physics will not alter the results significantly. Previous studies have shown that waves are more influential in the near-shore tidal zone and do not often travel upriver much beyond the tidal limit except in cases of extreme storm surge [23,45]. Therefore, the lack of waves will mostly affect the comparisons at the NOS stations but should have little to no bearing on the inland USGS results.…”
Section: Validation Of Model Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This is not a true "total water level" simulation, as waves were not included; however, as the focus of this study is to provide general proof of concept and validation of the methodology rather than a true hindcast validation of the near-shore coastal response, the lack of wave physics will not alter the results significantly. Previous studies have shown that waves are more influential in the near-shore tidal zone and do not often travel upriver much beyond the tidal limit except in cases of extreme storm surge [23,45]. Therefore, the lack of waves will mostly affect the comparisons at the NOS stations but should have little to no bearing on the inland USGS results.…”
Section: Validation Of Model Resultsmentioning
confidence: 97%
“…Previous work [23,45] has looked at connecting a hydrologic and hydrodynamic model in the North Carolina coast in the Tar-Neuse Pamlico areas. In particular, this work examined the behavior for the main stems of four different riverine areas in North Carolina: Tar and Neuse Rivers and Fishing and Contentnea Creeks but it did not include precipitation.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 72 articles corresponding to query 4, more than half of the articles (39) were excluded from the criteria analysis (Section 3.2) (Alipour et al, 2020;Azam et al, 2017;Chen et al, 2019;Chu et al, 2022;Ciavola et al, 2018;Davies, 2015;Ding & Fang, 2019;Dresback et al, 2019;Habibi et al, 2021;Han & Sharif, 2021;Hofmann & Schüttrumpf, 2019;Ibarreche et al, 2020;Jha & Afreen, 2020;Jubach & Tokar, 2016;Kellens et al, 2013;Khan et al, 2018;Kim & Han, 2020;Kruczkiewicz et al, 2021;Li et al, 2022;Liu, Shi, & Fang, 2022;Liu, Zhou, et al, 2022;Lo et al, 2015;Munawar, Hammad, & Waller, 2021;Munawar, Ullah, et al, 2021;Nakamura & Morioka, 2019;Ngo et al, 2018;Nguyen et al, 2021;Perera et al, 2020;Pielke et al, 2021;Prikryl et al, 2021;Rasquinho et al, 2013;Saravi et al, 2019;Smith & Rodriguez, 2017;Stamellou et al, 2021;Tammar et al, 2020;Tariq et al, 2022;Wang, Chen, et al, 2021;Wang, Kong, et al, 2021;…”
Section: Submission Of Queriesmentioning
confidence: 99%